Towards legal grounds of applying precaution measures to convicted persons in prisons of Ukraine - Охман, Ольга Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article analyzes the legal principles and the implementation of safety measures (physical force, special means and weapons) to the persons who are held in a detention facilities and penal institutions of the closed type in penal activity of Ukraine. Evidence-based measures directed to the existing problems in this area are proposed. Recent events in Ukraine (the use of physical force, special means and weapons to the activists in the Maidan Kyiv in November 2013 - February 2014) activated mentioned theoretical and applied problem also in the penal activity that is: the practice of security measures applying to the prisoners detained in detention centers (here and after - the jail) and penal institutions of a closed type (among such according to the requirements of Art. 11 of the Penal Code of Ukraine, are prisons and juvenile correctional facilities) shows that often the staff of the State penitentiary Service of Ukraine abuses this right and, in some places, exceeds its powers, which ultimately leads to a substantial violation of the rights and interests of people held in prison and prisoners serving a sentence of imprisonment. As it is established in this study, the determinants, which make this situation are an inadequate legal provision of this type of criminal activity in Ukraine, insufficient scientific role in explaining the legal grounds of applying precaution measures to prisoners in custody and convicted persons in prisons. Textbooks, manuals and scientific and practical comments to the Criminal Code of Ukraine and other doctrinal sources concerning this issue made a decisive impact on the selecting of the theme of this scientific research and defining its goals and objectives. The author concludes that under "legal grounds of implementation in Ukraine of physical sources, special means and weapons to inmates in prison" one can understand a system of laws and other legal acts determining their admissibility, established principles and rules governing the procedure and conditions of the correctional and correctional facilities’ staff regarding the use of these measures and means to persons serving sentences of imprisonment.